Happiness and Homonymy of Life in Plotinus. - María Zamora Calvo, José (Problems / Problemos, 2020)
This article analyses the Plotinian reconsideration of the link between the definition of happiness and the homonymy of life. To safeguard Platonism, Plotinus inverts the Aristotelian discussions of homonymy and its metaphysical implications, and presents the prior-posterior relationship in terms of progressive degradation. Happiness does not consist of "life" in general (understood in a univocal sense) nor of the "rational life" (understood as the sum of genus and specific difference); rather, it consists of the life that is situated in the ontologically first and most perfect degree, which is the life that pertains to intelligence and is consubstantial with it, and of which the other lives are progressively degraded derivations. The man who possesses the first and perfect life of the intelligible in actuality, like the gods, can be considered happy.